Public Health Threat: Detection of Undeclared Dexamethasone and Paracetamol in Jamu Marketed in Kudus, Indonesia - Luthfiana Nurulin Nafi’ah; Kadar Ismah; Yanulia Handayani; Gendis Purno Yudanti; Sukarno; Annis Rahmawaty; Alvina Beti Maulia (HM Publisher, 2025)
Jamu, Indonesia's traditional herbal medicine, holds significant cultural and medicinal value. However, the adulteration of jamu with undeclared synthetic drugs like dexamethasone and paracetamol poses a severe public health risk. This study aimed to qualitatively identify these drugs in jamu products circulating in Kudus City, Indonesia. Ten jamu samples, representing various brands and forms (powder, capsules), were purchased from local depots in Kudus. Samples were selected based on their indication for pain relief or anti-inflammatory properties, lack of BPOM (Indonesia's Food and Drug Authority) registration, or discrepancies between the registration number on the packaging and the BPOM database. Organoleptic analysis (odor, taste, color, form) was performed, followed by microscopic analysis to identify natural ingredients using their characteristic fragments. Finally, infrared spectroscopy was employed to detect the presence of dexamethasone and paracetamol. Nine out of ten samples displayed BPOM registration numbers that were not verifiable in the official BPOM database, while one sample lacked any registration number. Organoleptic analysis revealed that six samples exhibited distinct herbal odors, often associated with bitter-tasting jamu. Microscopic analysis confirmed the presence of 1-4 natural ingredients in each sample. Notably, infrared spectroscopy identified paracetamol in one sample. In conclusion, the study revealed a concerning trend of unregistered jamu products and adulteration with undeclared paracetamol in Kudus City. This highlights the need for stricter regulatory measures, enhanced surveillance, and public awareness campaigns to ensure the safety and efficacy of jamu.